2020
DOI: 10.1103/physrevresearch.2.023241
|View full text |Cite
|
Sign up to set email alerts
|

Stroboscopic quantum optomechanics

Abstract: We consider an optomechanical cavity that is driven stroboscopically by a train of short pulses. By suitably choosing the interpulse spacing we show that ground-state cooling and mechanical squeezing can be achieved, even in the presence of mechanical dissipation and for moderate radiation-pressure interaction. We provide a full quantum-mechanical treatment of stroboscopic backaction-evading measurements, for which we give a simple analytic insight, and discuss preparation and verification of squeezed mechanic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
(103 reference statements)
0
21
0
Order By: Relevance
“…For the prospective membrane described above, one reaches a backaction-dominated regime with S qba ≥ S th for S det ≈ 10 −30 m 2 /Hz. Eventually, one could use advanced quantum measurement protocols to evade quantum backaction [4,60].…”
Section: L021001-4mentioning
confidence: 99%
“…For the prospective membrane described above, one reaches a backaction-dominated regime with S qba ≥ S th for S det ≈ 10 −30 m 2 /Hz. Eventually, one could use advanced quantum measurement protocols to evade quantum backaction [4,60].…”
Section: L021001-4mentioning
confidence: 99%
“…The condition for hitting the quantum regime then reads, according to Ref. [101], χ 2π n T m /Q, which with our parameters becomes χ 0.4. Based on this analysis, strong enough stroboscopic measurements seem in reach.…”
Section: Pulsed Techniquesmentioning
confidence: 77%
“…The scheme was discussed in detail recently in Ref. [101]. The authors found that the requirement for the measurement strength can be relaxed in this case.…”
Section: Pulsed Techniquesmentioning
confidence: 99%
“…For the prospective membrane described above, one reaches a backaction-dominated regime with S qba ≥ S th for S det ≈ 10 −30 m 2 /Hz. Eventually, one could use advanced quantum measurement protocols to evade quantum backaction [3,59].…”
Section: Discussion and Outlookmentioning
confidence: 99%

Membrane-based scanning force microscopy

Hälg,
Gisler,
Tsaturyan
et al. 2020
Preprint
Self Cite